Straegi Peningkatan Pendapatan Asli Daerah (PAD) Melalui Intensifikasi dan Ekstensifikasi Penerimaan Pajak Parkir di Kabupaten X - Sri Yaumi; Lailatul Maghfiroh; Rina Sulistyowati; Bayu malikhul Askhar (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to analyze and describe the impact of the parking tax intensification strategy on Original Regional Income (PAD), analyze and describe the impact of the parking tax extensification strategy on Regional Original Income (PAD), analyze the obstacles faced by BAPENDA in implementing intensification and extensification strategies as an effort to increase Regional Original Income (PAD). The research method used in this research is a quantitative descriptive approach and data is collected through interviews and observation. The research results show that the parking tax intensification strategy has an impact on local revenue (PAD) but still needs to be improved because it has not met the target. The parking tax extensification strategy has an impact on local revenue (PAD) but is not yet effective. The obstacle faced by BAPENDA in carrying out intensification and extensification strategies is lack of taxpayer awareness.The efforts made by the government include conducting outreach and establishing communication with business actors and monitoring the conditions in the parking environment by looking at the bookkeeping reports of parking businesses.